Caffeine content of Nespresso® pod coffee. Issue 1 (March 2019) - Desbrow, Ben; Hall, Susan; Irwin, Christopher
Background: Little independent information on the caffeine content of the popular Nespresso ® coffee pod range exists. Aim: To quantify the caffeine content of Nespresso ® pod coffees. Methods: Initially, three serves (ristretto (S), espresso (M), lungo (L)) of two pod varieties (Livanto and Roma) were prepared on three different Nespresso ® machines (2 × U-Delonghi (1 × 5 years since purchase (old), 1 × recently purchased (new)), 1 × new Lattissima Pro (alternate)) using two different batches (sleeves). Caffeine content was then determined via triplicate samples using high-performance liquid chromatography. Differences in content (i.e. serve size, machine or sleeve) were determined via an analysis of variance or paired sample t -tests. Results: Coffees prepared on different machines or pods from different sleeves did not influence the caffeine content (old = 63 ± 13, new = 60 ± 8, alternate = 60 ± 10 mg·serve –1 ; p = 0.537, sleeveA = 63 ± 11, sleeveB = 59 ± 9 mg·serve –1 ; p = 0.134). Less caffeine was delivered in S (51 ± 7 mg·serve –1 ) compared to larger sizes (M = 66 ± 7 and L = 66 ± 10 mg·serve –1 ). Subsequently, the caffeine content from two serve sizes (S and L) from 17 other varieties within the Nespresso ® range was determined and compared to the manufacturer's values. Caffeine content (all pods) ranged from 19 to 147 mg·serve –1, and represented 51–162% of manufacturer's values. Conclusion: Nespresso ® consumers are exposed to variable amounts of caffeine, which often differ from the manufacturer's reports.